Les perspectives de la biodiversité en Afrique subsaharienne : repenser collectivement le modèle de gestion - Robert Kasisi (VertigO)
The signatory countries of the Convention on Biological Diversity set the objective of halting the decline of biodiversity by 2010, but as the target date arrived and passed, the status of biodiversity on the planet remained dismal. As the UN Decade for Biodiversity dawned by the Rio+20 Earth Summit in June 2012 and the UN Biodiversity Strategic Plan moves forward, this article contextualizes biodiversity prospects in sub-Saharan Africa by examining the history of interactions between African communities and the environment, from the pre-colonial period to today. It provides a critical analysis of the current biodiversity conservation planning methodologies and pinpoints several inherent obstacles, including the neo-Malthusianism that dominates the thinking of certain wildlife experts. Setting out an argument with far-reaching implications for the success of future conservation efforts all over the world, the author examines the basis of emerging conservation approaches in sub-Saharan Africa, focusing on the need to forge a more inclusive conservation practice and open up to the perceptions, representations and cultural universe of the Other.